Consumer perception in the use of financial technologies: Comparison of Turkey and Azerbaijan - SHALALA ASADOVA; EMINE EBRU AKSOY (Journal of Advanced Research in Social Sciences and Humanities, 2021)
Aim: The concept of financial technology, which grew out of the digitalization of the financial sector, is becoming more and more significant every day. This research examines how people in Turkey and Azerbaijan feel about using financial technologies and about seeing if those feelings vary depending on demographic factors. Method: This research employed surveys for this purpose in both countries. An overall sample size of 397 questionnaires was used for the study. The survey data were analyzed by the SPSS 22 software. Non- parametric tests were used to analyze the opinions of the general public. Findings: The tests’ results show that in both countries, consumers’ perspectives on the usefulness of financial technologies vary with age and level of education. Consumers in Turkey have a more negative outlook on the efficacy of financial technologies than those in Azerbaijan. That Turkey is closer to the developed world and smart capital and uses these sorts of business models more frequently than Azerbaijan may account for the disparity. Implications/Novel Contribution: This research provides information on consumer attitudes in two different countries. It illuminates the demographic factors that shape consumer preferences. There hasn’t been a lot of research done on this topic in either country.